The impact of shifts in marine biodiversity hotspots on patterns of range evolution: Evidence from the Holocentridae (squirrelfishes and soldierfishes). (19th December 2014) - Dornburg, Alex; Moore, Jon; Beaulieu, Jeremy M.; Eytan, Ron I.; Near, Thomas J.
<x xml:space="preserve">Abstract</x> One of the most striking biodiversity patterns is the uneven distribution of marine species richness, with species diversity in the Indo‐Australian Archipelago (IAA) exceeding all other areas. However, the IAA formed fairly recently, and marine biodiversity hotspots have shifted across nearly half the globe since the Paleogene. Understanding how lineages have responded to shifting biodiversity hotspots represents a necessary historic perspective on the formation and maintenance of global marine biodiversity. Such evolutionary inferences are often challenged by a lack of fossil evidence that provide insights into historic patterns of abundance and diversity. The greatest diversity of squirrelfishes and soldierfishes (Holocentridae) is in the IAA, yet these fishes also represent some of the most numerous fossil taxa in deposits of the former West Tethyan biodiversity hotspot. We reconstruct the pattern of holocentrid range evolution using time‐calibrated phylogenies that include most living species and several fossil lineages, demonstrating the importance of including fossil species as terminal taxa in ancestral area reconstructions. Holocentrids exhibit increased range fragmentation following the West Tethyan hotspot collapse. However, rather than originating within the emerging IAA hotspot, the IAA has acted as a reservoir for holocentrid diversity that originated in adjacent regions over deep evolutionary time scales.